Linking climate change and socioeconomic development to urban land use simulation: Analysis of their concurrent effects on carbon storage. (February 2020) - Yang, Hang; Huang, Junlong; Liu, Dianfeng
Abstract: Land use/cover change (LUCC) in the context of rapid urbanization process has exerted profound influences on carbon storage and ecosystem functions. Exploring the relationships between various urbanization patterns and carbon storage is conductive to developing scientific carbon storage polices. This study incorporated climate change and socioeconomic development into the urbanization process, and designed six future urbanization scenarios based on the combination of the Representative Concentration Pathways (RCPs) and the Shared Socio-economic Pathways (SSPs). A hierarchical framework that integrates system dynamic, land-use simulation and carbon storage evaluation models was proposed to predict urban land use change under six concurrent scenarios of climate and socioeconomic conditions, and examine their synergic effects on carbon storage. Hubei Province, a rapidly urbanized area in central China, was selected as a case study. The results show that the decline of carbon storage from 2015 to 2030 ranges from 16.40 Tg to 24.22 Tg under different scenarios, and the scenario featuring steady climate conditions, low population growth, moderate economic growth and high-quality urbanization (e.g., technology innovation) will better maintain carbon storage. Our findings also demonstrate the spatially heterogeneous patterns of carbon storage change at regional scale, and more severe carbon storage loss in the medium-sized cities than the metropolis. This study suggests that targeted ecological conservation strategies should be developed for different cities. Highlights: Carbon storage in Hubei will decline depending on different combination of RCPs and SSPs (−16.4~-24.22 Tg). The carbon storage change and its three main causes present spatially heterogeneous patterns. Medium-sized cities deserve more attention to mitigate carbon storage loss than Metropolis. Technological innovation and moderate socioeconomic growth better maintain carbon storage.